(untitled) (Fiep Bulletin - online, 2011)
This theoretical objective is to investigate different teaching methods related to the bounce during physical education classes at school. In this regard, the literature review brings the contribution of great authors and renowned doctors in the specificity of each one, allowing setting different effects of teaching methods applied. As a result it was found that the methods are of paramount importance, since they are given to students at an age when they are in phase transitions and discoveries. It appears that to develop motor skills, teachers fall to the responsibility to awaken the love for the sport with respect, but the interest of each student as a continuous, coordinated, conscious committed to comprehensive training, where body and mind is seen as a unit.